Galectin-9 Alleviates LPS-Induced Preeclampsia-Like Impairment in Rats via Switching Decidual Macrophage Polarization to M2 Subtype - Li, Zhi-Hui; Wang, Li-Ling; Liu, Hong; Muyayalo, Kahinho P.; Huang, Xiao-Bo; Mor, Gil; Liao, Ai-Hua (Frontiers in Immunology, 2019)
Dysfunction of decidual macrophages (DMs) is considered a critical event in the pathogenesis of pre-eclampsia (PE). T cell immunoglobulin mucin 3 (Tim-3) is an important negative regulatory molecule that induces immune tolerance by interacting with its ligand Galectin-9 (Gal-9) and thus modulating function of various immune cells, including macrophages. However, the regulatory effects of Tim-3/Gal-9 signaling on DMs polarization and its role in PE remain unclear. In this study, we established a PE-like rat model by administering 1.0 μg/kg lipopolysaccharide (LPS) to normal pregnant Sprague-Dawley rats via the tail vein at embryonic day 5 (E5). Apart from the pre-eclamptic manifestations, increased M1 subtype and decreased M2 subtype were observed at the maternal-fetal interface, as well as increased pro-inflammatory cytokines (TNF-α and IL-1β) and reduced anti-inflammatory cytokines (TGF-β and IL-10). Moreover, the expression of Tim-3 in DMs and that of Gal-9 at the maternal-fetal interface were reduced. After administration of recombinant Galectin-9 (rGal-9) protein, we found that liver and renal injuries and maternofetal placental functional deficiency, including inadequate trophoblast cells invasion, impaired spiral artery remodeling and fetal capillary development, were reversed. In addition, the polarization of DMs was inclined to M2 subtype, which was similar to the polarization of DMs in the control rats but contrary to the PE-like rats. Interestingly, at E9, the expression of Tim-3 in DMs and that of Gal-9 at the maternal-fetal interface were significantly increased in the rGal-9 protein intervention group. Taken together, our findings show that administration of rGal-9 protein can alleviate the PE-like rat manifestations induced by LPS. This finding may be related to the activation of the Tim-3/Gal-9 signaling pathway, which promotes DMs polarization dominantly shifting to M2 subtype. Moreover, upregulation of Tim-3 in DMs and Gal-9 at the maternal-fetal interface at E9 suggests that Tim-3/Gal-9 pathway may play some important roles in early pregnancy and even embryo development.